Who was first? : discovering the Americas - Freedman, Russell (Clarion Books, 2007)
Examines the evidence that indicates others may have traveled to the Americas before Columbus in 1492 including Viking ruins, Mayan stonework, and other mysterious objects found in New England that date before Columbus.